Time-resolved radiation dosimetry using a cerium and terbium Co-doped YAG crystal scintillator. (March 2023) - Basaif, A.; Oresegun, Adebiyi; Zubair, H.T.; Zin, Hafiz; Choo, K.Y.; Ibrahim, S.A.; Wang, Tingyu; Wen, Jianxiang; Gang, Dingpeng; Lewis, Elfed; Abdul-Rashid, H.A.; Bradley, D.A.
Abstract: Time-resolved radiation dosimetry is an important factor in ensuring dose delivery during radiotherapy is within the prescribed doses for treatment. One method for time-resolved radiation dosimetry is by radioluminescence (RL) measurement technique using doped-silica optical fibre scintillators. The benefits of RL measurement technique include the capability to measure in real-time, high spatial resolution, and greater adaptability. Additionally, time-resolved dosimetry can be achieved by employing suitable scintillators with short rise and decay time. Silica optical fibre scintillators when doped with suitable dopants, provides the temporal resolution required for pulse-by-pulse dosimetry. Yttrium Aluminium Garnet (YAG) crystal optical fiber doped with Cerium and Terbium are discussed as a possible scintillator for time-resolved radiation dosimetry. The Cerium and Terbium co-doped YAG crystal scintillator samples are irradiated under a 6 MV photon beam from a Elekta Synergy® LINAC. The irradiation doses ranged from 100 cGy/min to 600 cGy/min. The measurements were made using an RL system with a gating time of 1μs. Linear RL response to dose of the irradiated scintillator samples was shown with minimal detectable memory, no afterglow or plateau effects. A rise time of 189.3 ns and a decay time of 260 ns were recorded, indicating promising potential for time-resolved radiation dosimetry. Highlights: Investigation is made of time-resolved radiation dosimetry using Ce/Tb:YAG fibre. Linear Radioluminescence response to doses ranging from 100 cGy to 600 cGy. Good temporal resolution with rise time of 189.3 ns and a decay time of 260 ns.